Pengaruh Substitusi Puree Kersen (Muntingia calabura L.) dan Penambahan Wortel (Daucus carota) Terhadap Daya Terima Permen Jelly pada Anak Sekolah - Siti Fatimatus Shadiyah; Veni Inderawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Kersen and carrots are local fruits and vegetables that often found in Indonesia. Kersen contain antioxidant activity, and carrots contain vitamin A, that beneficial for body. The purpose of this study to determine effect of kersen puree substitution and addition of carrots on the acceptability of jelly candy. This study used a pure experimental method with a 3x2 factorial design, namely 3 levels of kersen puree (40%, 50%, and 60%) and 2 levels of carrots (25% and 50%). The panelists is school-age children at MI Tarbiyatush Shibyan, totaling 45 students. The hedonic test data were analyzed using two-way anova with Duncan's further test to determine the real difference. Interaction of kersen puree substitution and carrot addition affected the color, but not affect the aroma, taste, and elasticity of jelly candy. Jelly candy with F3G2 formula with 60% kersen puree substitution and 50% carrot addition was most preferred. In 100 grams of F3G2 formula, jelly candy contains 318 kcal energy, 62.10% glucose, 3.05% fiber, 88.60 mg beta-carotene, and 78.60% antioxidant activity. Based on these results, jelly candy with kersen puree substitution and carrot addition is beneficial for school-age children because contains high antioxidants and vitamin A.